Evaluation of the effect of topical and systemic ozone application in periodontitis: an experimental study in rats - Ebru Saglam; Suzan Bayer Alinca; Tugba Zengin Celik; Uguray Payam Hacisalihoglu; Mehmet Ali Dogan (University of São Paulo, 2019)
Abstract Objective: The goal of the present study was to determine the effect of systemic and topical ozone application on alveolar bone loss (ABL) by evaluating the effect of Hypoxia-inducible factor −1 alpha (HIF-1-α) and receptor activator of NF-kB ligand (RANKL)-positive cells on histopathological and immunohistochemical changes in a rat periodontitis model. Methodology: Thirty male Wistar rats were divided into three groups: 1) Group C (control group); 2) Group SO (systemic ozone group) and 3) Group TO (topical ozone group). Experimental periodontitis was induced with a 3/0 silk suture placed at the mandibular left first molars of rats, and the suture was removed 14 days later. Ozone gas was injected intraperitoneally (0.7 mg/kg) in SO group. Topical ozone application protocol was performed using an ozone generator at 80% concentration (4th grade) 90- degree probe for the duration of 30 s. Both ozone applications were carried out for two weeks at intervals of two days. Histomorphometric and immunohistochemical analysis were performed. Results: ABL was significantly lower in Group SO compared to Group C (p: 0.0052). HIF-1α- positive cells were significantly lower in Group TO than in Group C (p: 0.0043). RANKL-positive cells were significantly lower in Group SO and in Group TO compared to the control group (p: 0.0033, p: 0.0075, respectively). Conclusion: Both ozone applications decreased RANKL-positive cell counts, TO application decreased HIF-1-α positive cells counts, and SO application was found to be more effective in reducing ABL compared to control group.